Combination effect between gut microbiota and traditional potentially modifiable risk factors for first-ever ischemic stroke in Tujia, Miao and Han populations in China - Zhang, Na; Wang, Haoren; Wang, Xiaolei; Tian, Mengyuan; Tian, Yong; Li, Qi; Liang, Chengcai; Peng, Xiaowei; Ding, Jian; Wu, Xinrui; Tan, Hongzhuan (Frontiers in Molecular Neuroscience, 2022)
China has had explosive growth in ischemic stroke(IS) burden with significant ethnic and geographic disparities. The aim of this study was to explore the possible combination effect between gut microbiota and traditional potentially modifiable risk factors for IS among two ethnic minorities(Tujia and Miao) and the Han population. Herein we first used the 16S rRNA sequencing to compare the gut microbial compositions of 82 patients with first-ever IS versus 82 normal controls(NCs) among Han, Tujia and Miao people between May 1, 2018, and April 30, 2019, from Xiangxi Tujia and Miao Autonomous Prefecture in China. An additive model was used to study the interaction between traditional risk factors and gut microbiota with R software. Linear Discriminant Analysis(LDA) and LDA Effect Size(LEfSe) results showed that the identified key gut microbiota’s taxonomic composition varied in different ethnicity between the IS patients and NCs. Furthermore, families Lactobacillaceae, Enterococcaceae, Streptococcaceae and Enterobacteriaceae were found to be positively correlated with high risk factors and negatively correlated with preventive factors in the IS patients, but families Ruminococcaceae and Lachnospiraceae was just the opposite in the NCs. There were additive interactions between traditional risk factors(systolic blood pressure, diastolic blood pressure and high-sensitive C-reactive protein) and family Enterococcaceae for first-ever ischemic stroke with the attributable proportion due to the interaction was 0.74, 0.71 and 0.85 respectively; and the synergy index was 4.45, 3.78 and 7.01 respectively. This preliminary but promising study showed that the gut microbiota disturbances may potentially interact to IS with different ethnic host’s traditional risk factors.